2012
DOI: 10.1371/journal.pone.0040987
|View full text |Cite
|
Sign up to set email alerts
|

Shrink-Induced Superhydrophobic and Antibacterial Surfaces in Consumer Plastics

Abstract: Structurally modified superhydrophobic surfaces have become particularly desirable as stable antibacterial surfaces. Because their self-cleaning and water resistant properties prohibit bacteria growth, structurally modified superhydrophobic surfaces obviate bacterial resistance common with chemical agents, and therefore a robust and stable means to prevent bacteria growth is possible. In this study, we present a rapid fabrication method for creating such superhydrophobic surfaces in consumer hard plastic mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
113
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 37 publications
1
113
0
Order By: Relevance
“…Electronic mail: afyee@uci.edu decreased bacterial adhesion on superhydrophobic hard plastics with roughened surfaces that have multiscale features transferred from heat-shrunken polyolefin film. 19 Along those lines, researchers found that nanorough titanium surfaces produced by electron beam evaporation decreased bacterial adhesion in comparison to unmodified, nanotubular, and nanotextured titanium surfaces. 20 In addition, nanophase ceramic surfaces (zinc oxide and titania) decreased bacterial adhesion more than microphase surfaces.…”
Section: Introductionmentioning
confidence: 97%
“…Electronic mail: afyee@uci.edu decreased bacterial adhesion on superhydrophobic hard plastics with roughened surfaces that have multiscale features transferred from heat-shrunken polyolefin film. 19 Along those lines, researchers found that nanorough titanium surfaces produced by electron beam evaporation decreased bacterial adhesion in comparison to unmodified, nanotubular, and nanotextured titanium surfaces. 20 In addition, nanophase ceramic surfaces (zinc oxide and titania) decreased bacterial adhesion more than microphase surfaces.…”
Section: Introductionmentioning
confidence: 97%
“…cells in general do not adhere to these surfaces. [22][23][24][25][26] This is a result of reduced protein adsorption required for initial cell adhesion. 27 Hydrophobic surfaces (with a 90 o >WCA<150 o ) are not generally antibiofouling and the level of bacterial adhesion to these surfaces depends greatly on other factors e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Topographical modification of the resultant surfaces with nano-and microstructures has emerged as a potential tool for the fabrication of functionalized surfaces with antibacterial properties [100]. Some of the technologies usually applied for fabrication of antibacterial surfaces via surface micro-and nanostructuring are chemical etching (Black Silicon), physical vapor deposition (PVD), plasma irradiation, hydrothermal treatments, photolithography, electron-beam lithography and ablation by ultrashort pulsed lasers [101][102][103][104][105][106][107]. In Table 4, the advantages and disadvantages of these micro and nano-patterning technologies are shown.…”
Section: Biocide Surface Treatmentsmentioning
confidence: 99%